APOPTOSIS IN IPSILATERAL KIDNEY. COMPARISON BETWEEN GROUP RECEIVING VERAPAMIL AND CONTROL GROUP POST-ARTIFICAL TOTAL UNILATERAL URETERAL OBSTRUCTION - Syahrir, Syakri; Soetojo, Soetojo; Santoso, Adi; Joewarini, Endang; P, Widodo J (Indonesian Urological Association, 2014)
Objective: Obstruction of the urinary tract has marked effects on renal blood flow, glomerular filtration rate (GFR), and tubular function. Ureteral obstruction results in an injury response that can progress to irreversible renal fibrosis and tubular damage by apoptosis. Materials and Methods: Forty five rabbits aged 13-17 weeks with body weights of 1250-1750 grams were divided into 4 groups. Group 1 underwent a sham operation and group 2 had unilateral ureteral ligation to cause total obstruction. Groups 3 and 4 also underwent unilateral ureteral ligation but with verapamil given on day 0 and day 7 respectively. Apoptosis to the renal tubules were assessed after nephrectomy on day 14 using immunohistochemistry by counting the number cell deaths/high power field (hpf). Results: The groups that received verapamil showed significantly less apoptosis compared to those without verapamil (2,73 vs 12,46 cell deaths/hpf; p<0,05). However, there was no significant difference between groups 3 and 4 (2,73 vs 2,89 cell deaths/hpf; p>0,05), although both groups still showed more cell deaths compared to group 1 (0,38 cell deaths/hpf). Conclusion: Verapamil appears to significantly decrease apoptosis during total unilateral ureteral obstruction. However, it cannot replace the benefit of relieving total obstruction